Low-Frequency Imaging of Fields at High Galactic Latitude with the Murchison Widefield Array 32 Element Prototype - Williams, C.; Hewitt, J.; Levine, A.; de Oliveira-Costa, A.; Bowman, Judd; Briggs, Frank; Gaensler, B.; Hernquist, Lars; Mitchell, D.; Morales, Miguel; Sethi, S.; Subrahmanyan, R.; et al. (Institute of Physics Publishing, Inc., 2012)
The Murchison Widefield Array (MWA) is a new low-frequency, wide-field-of-view radio interferometer under development at the Murchison Radio-astronomy Observatory in Western Australia. We have used a 32 element MWA prototype interferometer (MWA-32T) to observe two 50 degrees diameter fields in the southern sky, covering a total of similar to 2700 deg(2), in order to evaluate the performance of the MWA-32T, to develop techniques for epoch of reionization experiments, and to make measurements of astronomical foregrounds. We developed a calibration and imaging pipeline for the MWA-32T, and used it to produce similar to 15' angular resolution maps of the two fields in the 110-200 MHz band. We perform a blind source extraction using these confusion-limited images, and detect 655 sources at high significance with an additional 871 lower significance source candidates. We compare these sources with existing low-frequency radio surveys in order to assess the MWA-32T system performance, wide-field analysis algorithms, and catalog quality. Our source catalog is found to agree well with existing low-frequency surveys in these regions of the sky and with statistical distributions of point sources derived from Northern Hemisphere surveys; it represents one of the deepest surveys to date of this sky field in the 110-200 MHz band.